Two non-zero solutions for Sturm–Liouville equations with mixed boundary conditions. (June 2019) - D'Aguì, Giuseppina; Sciammetta, Angela; Tornatore, Elisabetta
Abstract: In this paper, we establish the existence of two non-zero solutions for a mixed boundary value problem with the Sturm–Liouville equation. The approach is based on a recent two critical point theorem.